2019
DOI: 10.3892/etm.2019.8054
|View full text |Cite
|
Sign up to set email alerts
|

Outcome prediction for patients with anterior circulation acute ischemic stroke following endovascular treatment: A single‑center study

Abstract: Previous studies have identified various factors associated with the outcomes of acute ischemic stroke (AIS) but considered only 1 or 2 predictive factors. The present study aimed to use outcome-related factors derived from biochemical, imaging and clinical data to establish a logistic regression model that can predict the outcome of patients with AIS following endovascular treatment (EVT). The data of 118 patients with anterior circulation AIS (ACAIS) who underwent EVT between October 2014 and August 2018 wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 39 publications
(45 reference statements)
0
12
0
Order By: Relevance
“…Although several predictors have been identified, such as age, NIHSS score, and preoperative glucose level, 13 14 postoperative laboratory indices, comprising serum glucose level and indictors of liver function (AGR, albumin), renal function (eGFR), and inflammation (blood neutrophil count, CRP), were strong predictors that have been neglected by existing prediction models. [3][4][5][6][7][8][9][10][11][12][13][14][15] In our study, we found that the predictive ability of postoperative laboratory indices outperformed that of preoperative indices and accounted for over half of the selected features in our model, highlighting the significant effects of postoperative conditions on outcomes following MT and suggesting that it should be evaluated in future studies. These factors are all from frequently recorded blood biochemistry tests or routine blood tests and, more importantly, are potentially modifiable.…”
Section: Discussionmentioning
confidence: 91%
“…Although several predictors have been identified, such as age, NIHSS score, and preoperative glucose level, 13 14 postoperative laboratory indices, comprising serum glucose level and indictors of liver function (AGR, albumin), renal function (eGFR), and inflammation (blood neutrophil count, CRP), were strong predictors that have been neglected by existing prediction models. [3][4][5][6][7][8][9][10][11][12][13][14][15] In our study, we found that the predictive ability of postoperative laboratory indices outperformed that of preoperative indices and accounted for over half of the selected features in our model, highlighting the significant effects of postoperative conditions on outcomes following MT and suggesting that it should be evaluated in future studies. These factors are all from frequently recorded blood biochemistry tests or routine blood tests and, more importantly, are potentially modifiable.…”
Section: Discussionmentioning
confidence: 91%
“…Clinical and MR factors also play an important role in outcome prediction of AIS. Previous studies have reported that the clinical variables, such as gender, age, and admission NIHSS, could be used as factors for predicting the outcome of AIS patients ( Kim and Vemuganti, 2015 ; Wu et al, 2019 ). To validate these results, we used the 90-day mRS > 2 as an unfavorable outcome criteria.…”
Section: Discussionmentioning
confidence: 99%
“…Patients who received first-line SR or the ADAPT therapy only were a prognosticator detected in our cohort. Many other predictive factors of good functional outcome have been proposed in previous studies, including age, successful revascularization, parenchymal hemorrhage, baseline NIHSS score, anterior choroidal artery infarction, stroke subtype (intracranial atherosclerotic disease or embolism), posterior circulation Acute Stroke Prognosis Early CT Score, diffusion-weighted imaging lesion volume, glucose on admission, and hypersensitive C-reactive protein ( 31 35 ). The difference in reported factors may result from the heterogeneity of the study designs and patient demographics.…”
Section: Discussionmentioning
confidence: 99%